Reproductive Health Issues (Texas Journal of Medical Science, 2022)
This article contains information on reproductive health, reproductive problems, the Law "On the protection of the reproductive health of citizens", signed by the President of the Republic of Uzbekistan on March 7, 2021, infertility, reproductive technologies, reproductive health protection